(Post-)Deuteronomistic Prohibition of Transvestitism (Deut 22:5)? The Question of Its Actual Meaning and Motivations - Lemański, Janusz (Collectanea Theologica, 2021)
Deut 22:5 marks the single instance of a prohibition of transvestitism in the Bible, and in its whole cultural milieu. The context in which it is situated suggests that it may have been inserted there as an addition, after the Babylonian captivity. That helps to narrow down the range of speculations as to the original Sitz im Leben of the law, and enables us to read it most of all within the canonical framework of the entirety of the Pentateuch. Hence, the precept pertains mainly to the principle of division of the human nature into the two sexes (Gen 1–2), the principle of retaining the order of creation (by not mixing kinds; Lev 19:19; Deut 22:9–11), and of keeping the procreational power, referred to here predominantly to masculinity (Gen 5:1–3; cf. Gen 1:28; 9:1.7).